Performing Exile: John Foxe's Christus Triumphans at Magdalen College, Oxford. Issue 4 (September 2016) - Blank, Daniel
Abstract: When Laurence Humphrey became President of Magdalen College, Oxford in 1561, one of his earliest endeavours was to commission a production of John Foxe's Christus Triumphans . Although it remains uncertain whether the play was actually performed, this article explores the implications of Humphrey's request, taking his interest in staging the play as a starting point for understanding the value Christus Triumphans held for a generation of returned Protestant exiles. I begin by placing Foxe's apocalyptic comedy alongside the writings of Marian Protestants, situating the play within the concerns of exile and demonstrating the particular importance of conversion to the Protestant cause. I then consider the circumstances of Humphrey's production at Magdalen, using key archival documents to illuminate what that performance might have looked like. Humphrey's proposed staging of Christus Triumphans not only elucidates the salient concerns of the play itself, but also reveals how drama became a potent religious tool at this crucial post‐Marian moment. By realigning the play's engagement with the conditions of religious persecution, Humphrey sought to imbue the play with a retrospective significance, carefully shifting its message for an audience of collegiate spectators. At the same time, his staging of the play reflected – and perhaps heralded – a new interest in the visual capacities of university performance, ultimately demonstrating the vitality and influence of neo‐Latin religious drama in the academic setting.